Legal certainty of land rights through electronic registration and electronic certificates in Sialang Buah Village, Serdang Bedagai Regency - Joy Zaman Felix Saragih; Rolib Sitorus; Ricky Banke; Japansen Sinaga; Johanes Parlindungan Damanik; M Arif (Priviet Social Sciences Journal, 2025)
This study examines the legal certainty of land rights through the implementation of electronic land registration and digital land certificates in Sialang Buah Village, Serdang Bedagai Regency. The digital transformation mandated by the Regulation of the Minister of Agrarian Affairs/National Land Agency No. 3 of 2023 marks a shift from conventional physical documents to integrated electronic land administration. Using a normative-empirical legal method supported by statute and conceptual approaches, this study analyzes the validity and legal certainty of electronic certificates and evaluates the readiness, acceptance, and socio-legal implications for rural communities. Data were collected through legal document analysis, field observations, and interviews with landowners, village officials, and the Land Office. The findings reveal that electronic certificates enhance authenticity, transparency, and administrative efficiency while strengthening public trust in the governance of land. However, challenges remain concerning digital literacy, infrastructure limitations, and the inclusion of vulnerable groups, which may trigger new forms of legal uncertainty in the future. This study concludes that electronic land registration effectively promotes legal certainty when accompanied by adequate public education, secure digital systems and inclusive implementation strategies. The results contribute to agrarian law development and provide policy insights for strengthening the equitable digital transformation of land governance.